Digital Literacy: Education for Safe Internet Usage - Nuning Kurniasih (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Digital literacy has an important role in preventing cybercrime. This Community Service Program (PKM) aims to increase public awareness of using the internet safely, positively and creatively. This PKM activities is a form of my participation as one of the speakers in the series of events "National Digital Literacy Movement" held by Ministry of Communication and Information of Republic of Indonesia (Kemkominfo) in collaboration with Siber Kreasi and Kemkominfo with House of Representative of Republic of Indonesia (DPR-RI). There are three Webinars discussed in this article. The target audience for the first meeting was the General Public in Pidie Regency, Aceh Province . The target audience for the second and third meetings was the General Public in Bandung and Cimahi of Indonesia. The technique of delivering training material used is lecture. The evaluation parameters in this Webinar are seen from the relevance of the Webinar participants' questions to the training material, feedback or responses to the training material, responses to the answers from the speaker and the enthusiasm of the Webinar participants. Based on my observations during the Webinar, the target audience seemed enthusiastic about participating in the training, understanding the training material and realizing that it is important to grow internet safely, positively and creatively from childhood.